Testing the dear enemy relationship in fiddler crabs: Is there a difference between fighting conspecific and heterospecific opponents? - Fogo, Bruno R. [UNESP]; Sanches, Fábio H.C. [UNESP]; Costa, Tânia M. [UNESP] (Elsevier, 2019)
Reduction of aggressiveness toward familiar neighbors, when compared to aggressiveness toward unfamiliar strangers, can decrease the costs of territory defense. This phenomenon is known as the “dear enemy effect”. Individuals may shift their aggressiveness toward neighbors or strangers from the same or different species, depending on the relative threat associated with different opponents. Therefore, a reduced level of aggressiveness between heterospecific neighbors is expected in relation to conspecific intruders, since the latter compete not only for territory, but also for mates. Herein we investigated the occurrence of the dear enemy effect in territorial fights between conspecific pairs of Leptuca leptodactyla and heterospecific pairs of L. leptodactyla versus Leptuca uruguayensis. Across both conspecific and heterospecific fights, medium- and high-intensity fight components were more used in resident–stranger than in resident–neighbor fights. Thus, residents showed a dear enemy response, regardless of opponent species. Moreover, conspecific fights induced a greater number of low- and medium-intensity fight components than did fights between heterospecifics, both neighbors and strangers. Finally, conspecific resident–stranger fights took longer than heterospecific resident–stranger fights. Our results indicate that fiddler crabs adjust their territorial response according to the species and resident status of intruders, consistent with the risks posed by different intruder types.
Keywords: Aggressiveness; Interspecific competition; Intraspecific competition; Opponent recognition; Territoriality